PERTAUTAN KEPENTINGAN ANTAR ELIT : STUDI TARIK ULUR KEPENTINGAN POLITIK ANTAR ELIT DALAM PEMBENTUKAN KABUPATEN PANGANDARAN - Fitriyani Yuliawati; Subhan Agung (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
Society certainly crave a more prosperous life, safe, peaceful, able to feed their family properly and wants other ideal. In today's the countries in the world of hopes and ideals via a mechanism known system and democracy. New mechanisms are emerging as the insistence of the Reformation is the insistence of Indonesia's regions to secede from the parent that we often refer to as autonomy. Insistence that gave birth to hundreds of new areas, both at the provincial and district / city emerged in Indonesia today. On one hand if we look at it positively, it is possible as the manifesto of a high sense of community ownership of their respective regions as well as the willingness to self-determination. On the other hand new problems arise as well as political risk, which appears sectarianism